Novel Technologies for Processing Mushrooms and its Marketing Strategies - Shwetha Acharya; Vijay Tajane; Prof. Shubhangi (International Journal of Engineering and Management Research, 2021)
Mushroom (Agaricus bisporus) a noticeable umbrella-shaped fruiting body of certain fungi which grow vigorously. Mushrooms are highly enriched in protein, vitamins and marco-nutrients. Mushrooms are proven to have anti-allergic, anti-cholesterol, anti-tumor and anti-cancer qualities. The most desirable property of freeze-dried mushrooms such as the nutritional content and quality are maintained. The products shelf life is increased by using freeze drier from 12 days to 90 days. The mushroom cultivation is a viable and attractive activity and it does not require access to land and low investment too. The present study focused on analyzing the mushroom preservation techniques and producer's market potential by captivating consumer’s awareness. Self administered required to collect the primary data from consumers. SWOT analysis is used at the end to generate information and hypothesis testing is used for mathematical reasoning.